Implementation of Interactive Learning Approach in IPAS Learning - Nadya Erita Kusuma; Suratno (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe the implementation of interactive learning approaches in IPAS (Integrated Science and Social Studies) learning in Grade V of SDN Bagi 02, Madiun Regency. The research employs a descriptive qualitative method to examine the effectiveness and implications of integrating interactive learning strategies into IPAS learning environments. Through observations, interviews, and documentation, the study investigates how interactive learning methods are implemented, perceived, and experienced by both educators and students. From the research findings, it can be concluded that the implementation of interactive learning approaches significantly impacts IPAS learning in Grade V of SDN Bagi 02, Madiun Regency. Learners actively engage in the IPAS learning process, enhancing their understanding of material concepts, and can develop social skills through interaction with teachers and peers. This research provides further recommendations for development in terms of supporting interactive approach curriculum development and adequate resource allocation.